How Does Green Finance Affect CO2 Emissions? Heterogeneous and Mediation Effects Analysis - Wang, Jianda; Ma, Ying (Frontiers in Environmental Science, 2022)
The original intention of green finance advocacy is to provide financing support for energy conservation and emission-reduction activities. In this context, the carbon dioxide (CO2) emission-reduction effect is worth further discussion. To this end, by gauging the green finance index, we apply the econometric method to evaluate the impact of green finance on carbon emissions. We also discuss geographical heterogeneity and the impact channels. The main findings imply that: (1) China’s implementation of green finance is an effective measure to mitigate greenhouse gas emissions; in other words, green finance in China can effectively reduce carbon emissions; (2) both green finance and carbon emissions show significant geographical heterogeneity and asymmetry; only in the eastern and central regions, can green finance help alleviate the greenhouse effect; and (3) besides the direct effect, green finance can affect the greenhouse effect by promoting the rapid growth of the provincial economy, restraining the improvement of energy efficiency, and accelerating the optimization of the current industrial structure. Following the above three findings, we propose some policy suggestions related to green finance evolution and carbon emissions reduction.